'Peace with a Capital P': The Spectre of Communism and Competing Notions of 'Peace' in Britain, 1949–1960. Issue 1 (April 2017) - Barnett, Nicholas; Smith, Evan
Abstract : This article is concerned with different factions within the British peace movement during the 1950s and early 1960s, each of which gave the word 'peace' a different meaning. We argue that the movement was made up of several, often contradictory sections, and despite attempts by groups like the Peace Pledge Union to distance themselves from the communistcontrolled British Peace Committee, popular perceptions were tainted by association with communism until the mid-1950s. Following the onset of the H-bomb era, this taint lessened as people began to fear the destructiveness of hydrogen weapons. When the Campaign for Nuclear Disarmament formed in 1958 it became the predominant British organization opposed to nuclear weapons and achieved popularity because it limited its objective to nuclear disarmament whereas the Peace Pledge Union demanded the condemnation of all war.